Futile import of tRNAs and proteins into the mitochondrion of Trypanosoma brucei evansi - Paris, Zdeněk; Hashimi, Hassan; Lun, Sijia; Alfonzo, Juan D; Lukeš, Julius (Molecular and biochemical parasitology, 2011)
Trypanosoma brucei brucei has two distinct developmental stages, the procyclic stage in the insect and the bloodstream stage in the mammalian host. The significance of each developmental stage is punctuated by specific changes in metabolism. In the insect, T. b. brucei is strictly dependent on mitochondrial function and thus respiration to generate the bulk of its ATP, whereas in the mammalian host it relies heavily on glycolysis. These observations have raised questions about the importance of mitochondrial function in the bloodstream stage. Peculiarly, akinetoplastic strains of Trypanosoma brucei evansi that lack mitochondrial DNA do exist in the wild and are developmentally locked in the glycolysis-dependent bloodstream stage. Using RNAi we show that two mitochondrion-imported proteins, mitochondrial RNA polymerase and guide RNA associated protein 1, are still imported into the nucleic acids-lacking organelle of T. b. evansi, making the need for these proteins futile. We also show that, like in the T. b. brucei procyclic stage, the mitochondria of both bloodstream stage of T. b. brucei and T. b. evansi import various tRNAs, including those that undergo thiolation. However, we were unable to detect mitochondrial thiolation in the akinetoplastic organelle. Taken together, these data suggest a lack of connection between nuclear and mitochondrial communication in strains of T. b. evansi that lost mitochondrial genome and that do not required an insect vector for survival.
Keywords: DNA, Kinetoplast; Trypanosomiasis; DNA-Directed RNA Polymerases; RNA interference; proteiny; adenosintrifosfát; Mitochondria; DNA řízené RNA-polymerasy; RNA, Guide, Kinetoplastida; RNA Transport; Cell Nucleus; RNA transferová; Cell Communication; trypanozomiáza; Oxidative Phosphorylation; buněčné jádro; Organisms, Genetically Modified; RNA Interference; RNA, Transfer; geneticky modifikované organismy; Protein Transport; transport RNA; Adenosine Triphosphate; Glycolysis; guide RNA, Kinetoplastida; kinetoplastová DNA; glykolýza; Proteins; transport proteinů; oxidativní fosforylace; mitochondrie; Trypanosoma; mezibuněčná komunikace